2009
DOI: 10.1177/0731684409103148
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Mechanical and Interfacial Properties Between Jute and E-glass Fiber-reinforced Polypropylene Composites

Abstract: Jute fiber (hessian cloth)-reinforced polypropylene matrix composites (50 wt% fiber) were fabricated by compression molding. Tensile strength, tensile modulus, bending strength, bending modulus, and impact strength of the composites were found to be 48 MPa, 2.5 GPa, 56 MPa, 4.5 GPa, and 18 kJ/m2, respectively. Then E-glass fiber (woven)-reinforced polypropylene-based composites (50 wt% fiber) were fabricated and the mechanical properties were compared with those of the jute-based composites. It was revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 18 publications
(21 reference statements)
5
63
0
7
Order By: Relevance
“…This is mainly due to the characteristics observed by glass fibres such as their hydrophobic behavior and high fibre specific strength 2,10 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This is mainly due to the characteristics observed by glass fibres such as their hydrophobic behavior and high fibre specific strength 2,10 .…”
mentioning
confidence: 99%
“…Furthermore, Khan et al 2 reported that synthetic fibres may cause potential health problem to human beings when dealing/processing glass fibres particulates. Interestingly, natural fibres are gaining much attention among researchers namely to explore on the possibility in replacing synthetic fibres.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The polymer materials that are biodegradable now enjoying considerable popularity, especially from the standpoint of environmental protection [13]. In recent years, many research works were developed in the field of natural fiber reinforced composites for using in several applications [14]. Natural fibers having low density, availability, high toughness, acceptable specific strength, enhance energy recovery, low cost and biodegradability are used as reinforcements in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%